1986
DOI: 10.1247/csf.11.21
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte differentiation of 3T3-L1 cells in serum-free hormone-supplemented media: Effects of insulin and dihydroteleocidin B.

Abstract: ABSTRACT. We previously established a serum-free hormone-supplemented medium for the induction of adipocyte differentiation of 3T3-L1 cells (Gamou, S. and N. Shimizu. in "Growth and Differentiation of Cells in Defined Environment", H. Murakami et al., ed., Kodansha/Springer-Verlag, pp. 173-178, 1985). Under those conditions the stage of the cell's commitment to adipocyte differentiation was separated from the stage of expression of the adipocyte phenotype. In the current study, the relationship between cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
(19 reference statements)
1
8
0
Order By: Relevance
“…Insulin is also well-known to be a potent stimulator of adipogenesis in vitro (23,24). To the best of our knowledge, we here show for the first time that insulin treatment of diabetic animals can increase adipogenesis in situ.…”
Section: Discussionsupporting
confidence: 55%
“…Insulin is also well-known to be a potent stimulator of adipogenesis in vitro (23,24). To the best of our knowledge, we here show for the first time that insulin treatment of diabetic animals can increase adipogenesis in situ.…”
Section: Discussionsupporting
confidence: 55%
“…When Balbic3T3 T mouse preadipocytes were shifted to heparinized medium containing human plasma, Scott et al (1982) demonstrated the existence of two temporal states for coupling of growth arrest and differentiation (G and 6 ). More recently, Gamou and Shimizu (1985) developed serum-free, hormone-supplemented conditions under which the stage of cell commitment to adipocyte differentiation (G,) could be separated from the stage of expression of the adipocyte phenotype (Gd). However for these latter conditions, this conclusion does not appear clearly convincing because their methodology involves the presence of a high concentration of fetal calf serum during the phase of expression of adipocyte phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…To undergo adipose differentiation, confluent 3T3-F442A cells require approximately 48 h in a medium supplemented with fetal bovine serum (FBS), which typically has high adipogenic activity6, whereas 3T3-L1 cells additionally require methyl isobutyl xanthine (MIX) and dexamethasone (Dex) in FBS medium78. If 3T3-F442A cells are cultured in the absence of fetal bovine serum or growth hormone (non-adipogenic media), the cells do not undergo adipose differentiation6.…”
mentioning
confidence: 99%